Understanding money using historical evidence - Adam Brzezinski; Nuno Palma; François R. Velde (Federal Reserve Bank of Chicago, 2024)
Debates about the nature and economic role of money are mostly informed by evidence from the 20th century, but money has existed for millennia. We argue that there are many lessons to be learned from monetary history that are relevant for current topics of policy relevance. The past acts as a source of evidence on how money works across different situations, helping to tease out features of money that do not depend on one time and place. A close reading of history also offers testing grounds for models of economic behavior and can thereby guide theories on how money is transmitted to the real economy.
Keywords: E40; E50; N10; 330; monetary policy; monetary history; natural experiments; policy experiments; identification in macroeconomics